2007
DOI: 10.1523/jneurosci.0764-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Induced Plasticity in Auditory Spatial Representations Revealed by Electrical Neuroimaging

Abstract: Auditory spatial representations are likely encoded at a population level within human auditory cortices. We investigated learninginduced plasticity of spatial discrimination in healthy subjects using auditory-evoked potentials (AEPs) and electrical neuroimaging analyses. Stimuli were 100 ms white-noise bursts lateralized with varying interaural time differences. In three experiments, plasticity was induced with 40 min of discrimination training. During training, accuracy significantly improved from near-chanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 94 publications
(109 reference statements)
8
40
1
1
Order By: Relevance
“…Consequently, a non-parametric statistical test has to be conducted, wherein the dependent measure is the DISS between two maps at a given point in time, t. We and others have colloquially referred to this analysis as topographic ANOVA or TANOVA (e.g. [6,7,42,44,54,63,71], see also [29]), though we would immediately remind the reader that no analysis of variance is being conducted. Instead, TANOVA entails a non-parametric randomization test [34].…”
Section: Global Field Power: a Single Reference-independent Measure mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a non-parametric statistical test has to be conducted, wherein the dependent measure is the DISS between two maps at a given point in time, t. We and others have colloquially referred to this analysis as topographic ANOVA or TANOVA (e.g. [6,7,42,44,54,63,71], see also [29]), though we would immediately remind the reader that no analysis of variance is being conducted. Instead, TANOVA entails a non-parametric randomization test [34].…”
Section: Global Field Power: a Single Reference-independent Measure mentioning
confidence: 99%
“…In addition, these dependent measures can in turn be correlated with behavioral measures (e.g. [1,43,63]), behavioral/mental states (e.g. [26,28]), and/or parametric variations in stimulus conditions (e.g.…”
Section: Spatial Correlation-based Fitting and Its Dependent Measuresmentioning
confidence: 99%
“…The separate processing of spatial and non-spatial information confers advantages, such as a very rapid discrimination of sound categories (e.g. living vs. non-living; Murray et al, 2006, or the rapidly induced, positionspecific plasticity of spatial representations, Spierer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Ample task learning reports [15,17,19,21] using other training paradigms such as ITD/ILD training are well documented in the literature. The confusion matrix (stimulus response) showed that there was a decline of perceptual confusions in the post-training phase.…”
Section: Discussionmentioning
confidence: 99%
“…Though a review of the literature has ample of citations on the nature and consequences of spatial acuity deficits [11][12][13][14] , the remediation programs initialized at ameliorating the spatial difficulties are scanty. Some of the notable strides in enhancing spatial acuity have used interaural difference training [15][16][17][18][19][20][21] in remediating errors due to poor spatial processing. However, these strides have limitations on the effect size and the generalization of the findings to other related tasks.…”
Section: Introductionmentioning
confidence: 99%